2017
DOI: 10.18773/austprescr.2017.004
|View full text |Cite
|
Sign up to set email alerts
|

Medication charts in residential aged-care facilities

Abstract: SUMMARYAn aged-care facility should maintain a current, accurate and reliable record of the drugs prescribed and given to a resident. The correct use of a medication chart can meet this requirement.The hard-copy National Residential Medication Chart aims to provide a standard form for the prescription, dispensing and administration of drugs. In addition to providing a comprehensive record, it should facilitate communications between health professionals who are unlikely to visit aged-care facilities at the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…However, medications belonging to the high-risk medicines group (e.g., insulin and anticoagulants) can have a particularly serious clinical impact on patients if they are not administered. A system with electronic MARLs (eMARLs) has thus been suggested as a solution in previous research, so that care providers can easily access information about the pharmacotherapy and subsequently administer medication [19,32,33].…”
Section: Resultsmentioning
confidence: 99%
“…However, medications belonging to the high-risk medicines group (e.g., insulin and anticoagulants) can have a particularly serious clinical impact on patients if they are not administered. A system with electronic MARLs (eMARLs) has thus been suggested as a solution in previous research, so that care providers can easily access information about the pharmacotherapy and subsequently administer medication [19,32,33].…”
Section: Resultsmentioning
confidence: 99%
“…Discrepancies between nursing home medication charts, doctors' prescriptions and pharmacy dispensing profiles are known to occur, 18 so differences between DAA contents and nursing home charts may reflect problems with communication of information between prescribers, pharmacies and nursing homes, rather than DAA packing errors by pharmacies. 19 Carruthers, et al reported that a substantial number of DAA errors were associated with failure to provide prescriptions or failure to chart or communicate medication changes to the pharmacy. 11 Hussainy, et al stated that numerous errors may have occurred due to a lack of effective communication between the nursing homes and pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…They highlighted the advantage of having prescribers, aged-care staff and pharmacists working from a single record of medication order information. 1 Their article focused primarily on problems with paper medication charts, and suggested that electronic charts may address the problems.…”
mentioning
confidence: 99%